(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Chemical ocular injury is a common injury among the population of Bangladesh. This present study in aimed to evaluate the pattern of chemical ocular injury in our context. Methods: This cross-sectional observational study was done among 50 patients of chemical ocular injury by different substances between January and June 2013. After initial evaluation patients were also followed up for next 3 months to evaluate the visual outcome. Results: Male to female ratio was 1.7:1. Males between 21-30 years and 41-50 years were mostly affected whereas females of 41-50 were affected most. Most commonly affected occupation was service (36%) followed by housewives (22%) and majority (58%) were from low socio-economic conditions. Thirty five (70%) cases were alkali burn and remainder 15 (30%) were acid burn. Among alkali, hydrated lime Ca (OH)2 had highest percentage 82.8%. Most (46%) patients with good visual acuity i.e. 6/12 6/24 belongs to early (less than six hours) reporting time interval. It was found that 48% were grade I and 34% cases were grade II injury and other grades were not pronounced. Study showed that improvement of visual acuity after initial management and subsequent treatment was significant. Conclusion: Alkali burn is the common pattern of ocular injury in our country where lime is the common chemical substance. Early intervention is essential to avoid long term visual disability. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19418